2002
DOI: 10.1096/fj.02-0578fje
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia and osteopathy in mice with kidney‐specific megalin gene defect

Abstract: Megalin is an endocytic receptor highly expressed in the proximal tubules of the kidney. Recently, we demonstrated that this receptor is essential for the renal uptake and conversion of 25-OH vitamin D3 to 1,25-(OH)2 vitamin D3, a central step in vitamin D and bone metabolism. Unfortunately, the perinatal lethality of the conventional megalin knockout mouse model precluded the detailed analysis of the significance of megalin for calcium homeostasis and bone turnover in vivo. Here, we have generated a new mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(142 citation statements)
references
References 31 publications
3
136
0
3
Order By: Relevance
“…Subsequent studies confirmed the relevance of megalin as a renal retrieval pathway for carrier-bound lipophilic vitamins and hormones essential to prevent uncontrolled urinary loss of these important metabolites (Christensen and Birn, 2001;Muller et al, 2003;Verroust et al, 2002).…”
Section: Megalin a Receptor For Cellular Uptake Of Vitamin D Metabolmentioning
confidence: 93%
See 1 more Smart Citation
“…Subsequent studies confirmed the relevance of megalin as a renal retrieval pathway for carrier-bound lipophilic vitamins and hormones essential to prevent uncontrolled urinary loss of these important metabolites (Christensen and Birn, 2001;Muller et al, 2003;Verroust et al, 2002).…”
Section: Megalin a Receptor For Cellular Uptake Of Vitamin D Metabolmentioning
confidence: 93%
“…Absence of this DBP receptor pathway in megalin -/-mice results in an inability to retrieve 25-OH vitamin D 3 /DBP complexes from the primary urine and in aberrant excretion of the metabolite. As a consequence of urinary loss of the steroid, plasma levels of 25-OH vitamin D 3 and 1,25-(OH) 2 vitamin D 3 are decreased by more than 70%, resulting in plasma vitamin D deficiency and in bone calcification defects (Hilpert et al, 2002;Leheste et al, 2003;Nykjaer et al, 1999).…”
Section: Megalin a Receptor For Cellular Uptake Of Vitamin D Metabolmentioning
confidence: 99%
“…Cells were grown at 378C in a humidified air incubator equilibrated with 5% CO 2 . Female megalin-deficient and megalinexpressing mice were developed in the laboratory of Professor Thomas Willnow (21,22); they were bred and PCR screened in the laboratory of Professor Otto Boerman. Healthy male (ICR/CD1) mice were purchased from Harlan (Horst, The Netherlands).…”
Section: Cell Culture and Animal Modelsmentioning
confidence: 99%
“…The urinary loss of vitamin D results in growth retardation and excessive osteoblastic and osteoclastic activity (89). A kidney-targeted megalin knockout is viable; these animals have hypocalcemia and osteomalacia (91). With loss of CLC-5, the amount of megalin in the proximal tubule was reduced in Ϫ/y animals relative to ϩ/y (87).…”
Section: Dent Disease (X-linked Recessive Nephrolithiasis) Dent and mentioning
confidence: 99%